Modeling the expansion of generation of offshore wind energy in the northeast: Maximizing benefits for Brazil: ISBN 978-630-95064-9-8 - Fontgallad, Isabel (Technium Books, 2025)
The book: Modeling the expansion of generation of offshore wind energy in the northeast: Maximizing benefits for Brazil is published in Technium. This content was translated by Stella Park. Any suggestions concerning the book’s content may be sent to stellamaypark357@gmail.com